A Report on Gamma Radiation Induced Variation in Seed Characters of Cicer arietinum L. - Koche, Deepak; Saha, Archana Joshi (Department of Agronomy and Horticulture, IPB University, 2019)
Cicer arietinum L. (chickpea) is one of most popular and cheap source of plant protein and minerals worldwide. The present study was directed to induce variations in seed characters of chickpea “Vijay”, especially with reference to increase in its protein and mineral content using gamma radiations as mutagenic agent. M2 population of Cicer arietinum L. “Vijay” after post-harvest analysis revealed that 300 Gy dose of gamma radiations induced significant variations in seed characters including seed size, surface texture and seed coat color. Total nine mutants were identified differing from control in seed coat colors and categorized into four groups on the basis of seed size as normal, small, bold and extra bold; two groups on the basis of surface texture and wrinkled or smooth surface. The seed yield of all mutants was noted as 100-seed weight, which was corresponding with seed size. The biochemical analysis of the seed mutants in the form of protein, iron and zinc content indicates that, seeds with dark colored seed coat have higher level of protein and minerals as compare to control.